I eat the manofê so it is not forgotten : Local perceptions and consumption of native wild edible plants from seasonal dry forests in Brazil (2014)
Background: There is little information available on the factors influencing people's selection of wild plants for consumption. Studies suggest a suitable method of understanding the selection of edible plants is to assess people's perceptions of these resources. The use and knowledge of wild resources is disappearing, as is the opportunity to use them. This study analyzes people's perceptions of native wild edible plants in a rural Caatinga (seasonal dry forest) community in Northeast Brazil and the relationships between the use of these resources and socioeconomic factors.Methods: Semi-structured interviews with 39 people were conducted to form a convenience sample to gather information regarding people's perceptions of 12 native wild edible plant species. The relationships between variables were assessed by simple linear regression analysis, Pearson and Spearman correlation analyses, and in the case of nominal variables, contingency tables. The discourse of participants regarding their opinions of the use of wild plants as food was analyzed through the collective subject discourse analysis technique.Results: Perceptions were classified into 18 categories. The most cited category was organoleptic characteristics of the edible part more specifically, flavor. Flavor was the main positive perception associated with plant use, whereas the negative perception that most limited the use of these plants was cultural acceptance. Perceptions of the use of wild edible plants were directly correlated with both interviewee age and income.Conclusion: Within the studied community, people's perceptions of native wild edible plants are related to their consumption. Moreover, the study found that young people have less interest in these resources. These findings suggest that changing perceptions may affect the conservation of plants, traditional practices and the associated knowledge. © 2014 Cruz et al.; licensee BioMed Central Ltd.